TNFα protein, DNA methylation, mRNA and miRNA expression evaluation in multiple sclerosis - Costantini, E.; Greig, N. H.; Aielli, L.; Silva, P. C.; Di Carlo, M.; Konstantinidou, F.; Reale, M. (Frontiers in Molecular Biosciences, 2025)
BackgroundTumor necrosis factor alpha (TNFα) is a key cytokine involved in the inflammatory and neurodegenerative processes underlying multiple sclerosis (MS). Its expression is finely regulated by epigenetic and post-transcriptional mechanisms, including promoter methylation and miRNA activity. The objective of this study is to investigate TNFα expression, promoter methylation, and its regulation by miR-130a-3p in patients with relapsing–remitting (RR)MS, evaluating both serum and saliva as potential diagnostic biofluids.MethodsRRMS patients in clinical remission and sex and age-matched healthy controls (HC) were enrolled. TNFα levels were quantified in serum, peripheral blood mononuclear cell (PBMC) supernatants, and saliva using ELISA. TNFα mRNA expression and promoter methylation were analyzed by qPCR and pyrosequencing, respectively. Bioinformatic tools (TargetScan, miRTargetLink 2.0, miEAA 2) were used to explore miRNA–TNFα interactions, and miR-130a-3p expression was evaluated in serum and saliva by qPCR.ResultsRRMS patients showed significantly higher TNFα mRNA and protein levels compared to HC, paralleled by significant hypomethylation of the TNFα promoter in PBMCs. miR-130a-3p was markedly downregulated in both serum and saliva, exhibiting an inverse trend with TNFα expression. Salivary TNFα levels mirrored serum alterations, supporting the feasibility of saliva as a noninvasive biomarker source.ConclusionThe data indicate that TNFα upregulation in RRMS is associated with promoter hypomethylation and reduced miR-130a-3p expression, suggesting a coordinated epigenetic and post-transcriptional control of this cytokine. The parallel trends observed in saliva and serum highlight the potential use of salivary TNFα and miR-130a-3p as minimally invasive biomarkers for MS monitoring and early diagnosis.